Study on Boiling Performance of Multi-bubble Nucleation at Nanoscale - GAO Deyang, SUN Zhiyuan, LIU Zhanwei, BO Hanliang (Yuanzineng kexue jishu)
Boiling is an intense phase change process that effectively utilizes the latent heat of the liquid, making it a critical mechanism in applications with high heat transfer demands, such as electronic device thermal management, chemical engineering, and nuclear reactor heat exchangers. In nuclear engineering, boiling phenomena are ubiquitous in several mainstream reactor types, including pressurized water reactors (PWR), boiling water reactors (BWR), and low-temperature heating reactors. Boiling not only enhances heat transfer performance but also impacts reactor coolant density through bubble nucleation and growth processes, potentially leading to reactivity fluctuations. Thus, understanding bubble formation and growth dynamics is of significant research interest. Molecular dynamics simulations provide a powerful tool for investigating bubble nucleation, microscopic bubble behavior, and heat transfer mechanisms at the nanoscale. However, current nanoscale research often overlooks the differences between simultaneous bubble growth processes and the effects of bubble coalescence on heat transfer performance. This study visually explored the nucleation process of bubbles on surfaces with varying wettabilities and multiple nucleation sites. A quantitative analysis was performed on the influence of wettability and nucleation site spacing on key parameters, such as nucleation time, liquid temperature at nucleation, bubble volume growth rate, and surface heat transfer performance. The results show that multiple nucleation sites exert mutual compression, leading to variations in bubble sizes. As nucleation site spacing increases, the bubble volume growth rate increases significantly. On nanostructured surfaces, nucleation occurs earlier and at lower liquid temperatures compared to smooth surfaces. This is attributed to the enhanced heat accumulation in nanopits, which enables atoms to acquire sufficient energy to overcome the potential energy barrier and trigger earlier nucleation. Furthermore, hydrophilicity exerts dual effects on nucleation. While strong solid-liquid interactions accelerate heat absorption on hydrophilic surfaces, they also create a higher potential energy barrier that impedes nucleation. However, in general, hydrophilic surfaces tend to nucleate earlier. Finally, premature bubble coalescence limits the utilization of the fluid’s latent heat. As nucleation site spacing increases, the critical heat flux increases significantly, with a maximum difference of up to 19.6%. On surfaces with lower hydrophilicity, smooth surfaces exhibit superior heat transfer performance. This study provides a theoretical basis for optimizing the microstructural design in the boiling heat transfer process, offering valuable guidance for the design of efficient heat exchange systems such as nuclear reactors.